Frenzy - Cooper, Ian (Freelance writer) (Leighton Buzzard : Auteur, 2018)
Frenzy is perhaps Hitchcock's most nakedly autobiographical film, representing both a comeback and farewell to the city of his birth. Ian Cooper discusses the evolution of the film, its production, reception, and place in Hitchcock's oeuvre, as well as its status as a key film of ""sleazy Seventies"" British cinema.
Amuse-bouche -- The starter -- Entrée -- Main course -- Last supper -- Bibliography.
Includes bibliographical references (pages 89-94) and index.
Online resource; title from digital title page (viewed on June 18, 2018).
JSTOR
Keywords: Frenzy (Motion picture); Hitchcock, Alfred, -- 1899-1980 -- Criticism and interpretation; Hitchcock, Alfred, -- 1899-1980; Frenzy (Motion picture); Criticism, interpretation, etc